Study on column leaching process of rare earths from ion adsorption clays by ammonium sulfate - Nguyen , Van Tung; Bui , Ba Duy; Cao, Duy Minh; Nguyen , Thi Lien; Luu , Xuan Dinh (Nuclear Science and Technology, 2026)
This report presents the results of study on the column leaching process of rare earths from ion adsorption clay by ammonium sulfate at laboratory scale. Total rare earths content in ion adsorption clay about 350 - 550 ppm. The influence of factors such as solution concentration (NH4)2SO4, time leaching, solid/liquid ratio, number of stage washing ... on the rare earth recovery efficiency was evaluated. The obtained results showed that the rare earth recovery efficiency was up to about 90% under optimal conditions. The obtained technological parameters will re-evaluated at pilot scale (500 kg/batch) to assess the possibility of larger scale development.